Transcriptional Repression of MFG-E8 Causes Disturbance in the Homeostasis of Cell Cycle Through DOCK/ZP4/STAT Signaling in Buffalo Mammary Epithelial Cells - Verma, Arvind K.; Ali, Syed A.; Singh, Parul; Kumar, Sudarshan; Mohanty, Ashok K. (Frontiers in Cell and Developmental Biology, 2021)
The mammary gland is a unique apocrine gland made up of a branching network of ducts that end in alveoli. It is an ideal system to study the molecular mechanisms associated with cell proliferation, differentiation, and oncogenesis. MFG-E8, also known as Lactadherin, is a vital glycoprotein related to the milk fat globule membrane and initially identified to get secreted in bovine milk. Our previous report suggests that a high level of MFG-E8 is indicative of high milk yield in dairy animals. Here, we showed that MFGE-E8 controls the cell growth and morphology of epithelial cells through a network of regulatory transcription factors. To understand the comprehensive action, we downregulated its expression in MECs by MFG-E8 specific shRNA. We generated a knockdown proteome profile of differentially expressed proteins through a quantitative iTRAQ experiment on a high-resolution mass spectrometer (Q-TOF). The downregulation of MFG-E8 resulted in reduced phagocytosis and cell migration ability, whereas it also leads to more lifespan to knockdown vis-a-vis healthy cells, which is confirmed through BrdU, MTT, and Caspase 3/7. The bioinformatics analysis revealed that MFG-E8 knockdown perturbs a large number of intracellular signaling, eventually leading to cessation in cell growth. Based on the directed network analysis, we found that MFG-E8 is activated by CX3CL1, TP63, and CSF2 and leads to the activation of SOCS3 and CCL2 for the regulation of cell proliferation. We further proved that the depletion of MFG-E8 resulted in activated cytoskeletal remodeling by MFG-E8 knockdown, which results in the activation of three independent pathways ZP4/JAK-STAT5, DOCK1/STAT3, and PIP3/AKT/mTOR. Overall, this study suggests that MFG-E8 expression in mammary epithelial cells is an indication of intracellular deterioration in cell health. To date, to the best of our knowledge, this is the first study that explores the downstream targets of MFG-E8 involved in the regulation of mammary epithelial cell health.